2000
DOI: 10.1006/viro.2000.0561
|View full text |Cite
|
Sign up to set email alerts
|

Pseudosubstrate Inhibition of Protein Kinase PKR by Swine Pox Virus C8L Gene Product

Abstract: The interferon-induced protein kinase PKR is activated upon binding double-stranded RNA and phosphorylates the translation initiation factor eIF2alpha on Ser-51 to inhibit protein synthesis in virally infected cells. Swinepox virus C8L and vaccinia virus K3L gene products structurally resemble the amino-terminal third of eIF2alpha. We demonstrate that the C8L protein, like the K3L protein, can reverse the toxic effects caused by high level expression of human PKR in yeast cells. In addition, expression of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Substitution of Ser-51 in eIF2␣ by Ala suppresses PKR toxicity as do mutations that block kinase activity (9,14,15). Coexpression of the vaccinia virus K3L protein or the related swinepox virus C8L protein suppresses PKR toxicity in yeast (16,17). Consistent with the notion that the K3L protein is a PKR pseudosubstrate inhibitor, mutations targeting residues in the K3L OB-fold domain that are conserved in eIF2␣ impaired K3L inhibition of PKR both in yeast (17) and in vitro (4).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Substitution of Ser-51 in eIF2␣ by Ala suppresses PKR toxicity as do mutations that block kinase activity (9,14,15). Coexpression of the vaccinia virus K3L protein or the related swinepox virus C8L protein suppresses PKR toxicity in yeast (16,17). Consistent with the notion that the K3L protein is a PKR pseudosubstrate inhibitor, mutations targeting residues in the K3L OB-fold domain that are conserved in eIF2␣ impaired K3L inhibition of PKR both in yeast (17) and in vitro (4).…”
mentioning
confidence: 69%
“…Previously, we showed that high-level expression of human PKR under the control of a yeast galactose-inducible promoter was toxic in yeast, and that this toxicity was suppressed by coexpression of the vaccinia virus K3L protein. In addition, we identified the K3L-H47R mutant as a more potent inhibitor of PKR (16,17). To facilitate screening for PKR mutants resistant to K3L inhibition, the DNA fragment encoding the galactose-inducible GAL-CYC1 promoter and the K3L-H47R ORF was subcloned to a yeast-integrating vector.…”
Section: Screen To Identify Pkr Mutants Resistant To Inhibition By Thmentioning
confidence: 99%
“…Elucidating the mechanism by which PKR function is subverted by viral products has enhanced our understanding of how PKR and other eIF2α family kinases naturally function. In particular, viral mimicry appeared as a recurring theme: analysis of the pseudosubstrate inhibitor K3L from vaccinia virus revealed key molecular determinants required for PKR recognition of its natural substrate eIF2α (10)(11)(12); analysis of the RNA binding protein E3L from vaccinia virus revealed how PKR itself senses dsRNA through comparable infrastructure (13)(14)(15); and analysis of the RNA inhibitor VAI from adenovirus showed how a structured RNA decoy can competitively engage the dsRNA-binding domains of PKR in a manner that circumvents kinase domain activation (16)(17)(18).…”
Section: Significancementioning
confidence: 99%
“…Vaccinia virus uses two strategies to evade PKR. First is expression of E3L, which binds and masks dsRNAs (26). The second is expression of K3L, which binds and inhibits PKR via its ability to mimic the natural substrate of this enzyme, eIF2␣ (26).…”
Section: Rnai In Embryonic Stem Cellsmentioning
confidence: 99%